COVID-19 : An Opportunity to Create a Comprehensive and Holistic Indian Management Perspective - Pillania, Rajesh K. (Prabandhan: Indian Journal of Management, 2020)
We should use the COVID-19 as an opportunity to create a comprehensive and holistic Indian management perspective. There are a number of arguments behind it such as our success for many centuries as a culture and as an economy, importance of culture and context, availability of rich literature, lack of a comprehensive and holistic Indian management perspective, and lastly, using COVID-19 as a shock therapy to get out of the business as usual mode. To be an economic superpower, we need to bring something new, which is unique to us, with which we can relate, can embrace, and can enjoy for a long time. This opinion paper has important implications for practitioners, academicians, and researchers.